2020
DOI: 10.1371/journal.pone.0228370
|View full text |Cite
|
Sign up to set email alerts
|

The long-term effects of a family based economic empowerment intervention (Suubi+Adherence) on suppression of HIV viral loads among adolescents living with HIV in southern Uganda: Findings from 5-year cluster randomized trial

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 49 publications
1
48
0
Order By: Relevance
“…Tested using randomized controlled trials, results indicate that this program is effective in reducing children's economic barriers to attend school, supporting the argument that such programs can address family-level and child poverty, which could in turn improve health outcomes. More specifically for YLWHIV, in a large sample of Ugandan adolescents between the ages of 10 and 16 years and living with HIV, the intervention was found to significantly improve viral suppression, the primary marker of ART adherence (61,62). It is possible that the promotion of financial stability may have addressed transport costs and food security, both of which are factors identified as barriers to ART adherence (63)(64)(65)(66).…”
Section: Current Interventions and The Potential Role Of Socio-econommentioning
confidence: 99%
“…Tested using randomized controlled trials, results indicate that this program is effective in reducing children's economic barriers to attend school, supporting the argument that such programs can address family-level and child poverty, which could in turn improve health outcomes. More specifically for YLWHIV, in a large sample of Ugandan adolescents between the ages of 10 and 16 years and living with HIV, the intervention was found to significantly improve viral suppression, the primary marker of ART adherence (61,62). It is possible that the promotion of financial stability may have addressed transport costs and food security, both of which are factors identified as barriers to ART adherence (63)(64)(65)(66).…”
Section: Current Interventions and The Potential Role Of Socio-econommentioning
confidence: 99%
“…Compared to adults and children, ALHIV have worse outcomes across the HIV care continuum, with lower testing, antiretroviral therapy (ART) coverage, and viral suppression rates [3][4][5][6]. Data from the Population-based HIV Incidence Assessments (PHIA) conducted in Eswatini, Lesotho, Malawi, Zambia and Zimbabwe found that only 56% (95% CI 50-62) of ALHIV 15-19 years were aware of their HIV-positive status; among ALHIV with known status, 50% (95% CI [44][45][46][47][48][49][50][51][52][53][54][55][56] were on ART and only 35% (95% CI 30-41%) on ART had a suppressed HIV viral load (VL<50 copies/mL) [7]. As a result of the low coverage and uptake of services, HIV is the leading cause of death for adolescents 10-19 years of age in SSA [1].…”
Section: Introductionmentioning
confidence: 99%
“…For six years (2012-2018), the Suubi+Adherence study team prospectively followed 702 youth living with HIV (YLHIV; aged 10 to 16 years at enrollment) across 39 clinics in Uganda testing the impact of a family economic empowerment (FEE) intervention comprising an incentivized youth financial savings account (YSA) augmented with financial literacy training (FLT) and peer mentorship [ 3 ]. Our study findings pointed to superior short-term viral suppression and positive child health and mental health functioning among the intervention arm receiving the FEE intervention compared to the control arm [ 4 7 ]. This study proposes to examine whether the results are maintained through young adulthood, an incredibly vulnerable transition period [ 8 ], particularly in areas of cognitive development, mental health, sexual risk taking behaviors and alcohol/drug misuse [ 9 12 ].…”
Section: Introductionmentioning
confidence: 89%
“…The Suubi+Adherence study findings, however, advanced knowledge in regards to short-term outcomes; used rigorous objective measures, i.e. biomarkers (viral suppression) [ 7 ] and unannounced pill counts, and included a cost-effectiveness analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation